Pengaruh Kombinasi Kompres Dingin dan Mindfulness Spiritual Islami (MSI) Terhadap Penurunan Nyeri Post Operasi Pada Pasien Fraktur di Instalasi Rawat Inap (Post Bedah) RSUD Dr. R. Sosodoro Djatikoesoemo Bojonegoro - Futukhah, Ainun; Faridah, Virgianti Nur; Pramestirini, Rizky Asta (Jurnal Keperawatan Muhammadiyah, 2025)
Introduction: Pain is a prevalent clinical issue among postoperative fracture patients, significantly impacting their overall quality of life. Effective pain management is therefore essential and may encompass both pharmacological and non-pharmacological interventions. One non-pharmacological approach that has demonstrated therapeutic potential is the combination of cold compress application and Islamic Spiritual Mindfulness (MSI). This study aims to evaluate the impact of integrating cold compress therapy with Islamic Spiritual Mindfulness on postoperative pain alleviation in fracture patients treated at Dr. R. Sosodoro Djatikoesoemo Regional General Hospital, Bojonegoro. Method: The research employed a pre-experimental design using a one-group pre-posttest approach, with a total population of 92 patients and a sample size of 38 respondents, selected through consecutive sampling. The study utilized the Numeric Rating Scale (NRS) and Standard Operating Procedures (SOP) as research instruments. A normality test indicates p < 0.05, signifying non-normal data distribution, necessitating hypothesis testing via the Wilcoxon signed-rank test. Results: The findings revealed that, prior to intervention, 100% of patients experienced severe pain. Following the intervention, the majority of respondents (79.2%) reported a reduction in pain intensity to a moderate level. Analyse: The Wilcoxon test results indicate statistical significance (p = 0.000), confirming the effectiveness of the combined cold compress and Islamic Spiritual Mindfulness therapy in mitigating postoperative pain severity in fracture patients at Dr. R. Sosodoro Djatikoesoemo Regional General Hospital, Bojonegoro. Conclusion: These findings suggest that incorporating cold compress therapy and Islamic Spiritual Mindfulness may serve as a viable complementary strategy for postoperative fracture pain management.